Evolution of DNA Technology in Treating Animal Diseases - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammad (Darul Yasin Al Sys, 2025)
A single gene mutation can result in aberrant cell activity and the production of a faulty protein. The cell will certainly operate very poorly or not at all as a result of this mutation. Given that the genetic material may be a therapeutic agent; this might be seen as qualitatively distinct from other conventional drugs. Gene therapy may be able to rectify or perhaps cure the pathophysiology of a disease by changing the genetic composition of cells. In veterinary medicine, genetic engineering has been used to xenografts, and detects, prevent, and treat illnesses. Among the challenges that gene therapy faces include transfection, intracellular vector stability, cellular and nuclear entrance, and ethical concerns. Deficits in gene transfer vectors and a lack of knowledge about the biological interactions between these vectors and the host are two examples of fundamental challenges.